ALG-bFGF Hydrogel Inhibiting Autophagy Contributes to Protection of Blood-Spinal Cord Barrier Integrity via PI3K/Akt/FOXO1/KLF4 Pathway After SCI - Renkan Zhang; Ling Xie; Fangfang Wu; Ji Xu; Leilei Lu; Lin Cao; Lei Li; Weiyang Meng; Hongyu Zhang; Chuxiao Shao; Xiaokun Li; Daqing Chen (Frontiers Media S.A., 2022)
Promoting blood-spinal cord barrier (BSCB) repair at the early stage plays a crucial role in treatment of spinal cord injury (SCI). Excessive activation of autophagy can prevent recovery of BSCB after SCI. Basic fibroblast growth factor (bFGF) has been shown to promote BSCB repair and locomotor function recovery in SCI. However, the therapeutic effect of bFGF via direct administration on SCI is limited because of its rapid degradation and dilution at injury site. Based on these considerations, controlled release of bFGF in the lesion area is becoming an attractive strategy for SCI repair. At present, we have designed a sustained-release system of bFGF (called ALG-bFGF) using sodium alginate hydrogel, which is able to load large amounts of bFGF and suitable for in situ administration of bFGF in vivo. Here, traumatic SCI mice models and oxygen glucose deprivation (OGD)-stimulated human brain microvascular endothelial cells were performed to explore the effects and the underlying mechanisms of ALG-bFGF in promoting SCI repair. After a single in situ injection of ALG-bFGF hydrogel into the injured spinal cord, sustained release of bFGF from ALG hydrogel distinctly prevented BSCB destruction and improved motor functional recovery in mice after SCI, which showed better therapeutic effect than those in mice treated with bFGF solution or ALG. Evidences have demonstrated that autophagy is involved in maintaining BSCB integrity and functional restoration in animals after SCI. In this study, SCI/OGD exposure-induced significant upregulations of autophagy activation-related proteins (Beclin1, ATG5, LC3II/I) were distinctly decreased by ALG-bFGF hydrogel near the baseline and not less than it both in vivo and in vitro, and this inhibitory effect contributed to prevent BSCB destruction. Finally, PI3K inhibitor LY294002 and KLF4 inhibitor NSC-664704 were applied to further explore the underlying mechanism by which ALG-bFGF attenuated autophagy activation to alleviate BSCB destruction after SCI. The results further indicated that ALG-bFGF hydrogel maintaining BSCB integrity by inhibiting autophagy activation was regulated by PI3K/Akt/FOXO1/KLF4 pathway. In summary, our current study revealed a novel mechanism by which ALG-bFGF hydrogel improves BSCB and motor function recovery after SCI, providing an effective therapeutic strategy for SCI repair.